2017
DOI: 10.1017/s095026881700214x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for Dengue virus (DENV) infection in the first 2 years of life in a Brazilian prospective birth cohort

Abstract: This study assessed the incidence and risk factors for dengue virus (DENV) infection among children in a prospective birth cohort conducted in the city of Recife, a hyperendemic dengue area in Northeast Brazil. Healthy pregnant women (n = 415) residing in Recife who agreed to have their children followed were enrolled. Children were followed during their first 24 months of age (May/2011-June/2014), before the 2015 Zika virus outbreak. DENV infection was detected by reverse-transcriptase polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Different ethnicities have been related to the risk of DENV infection. In Brazil, another study performed in Pernambuco identified that children born to mothers of Caucasian/Asian descent had a high risk of dengue [12]. In Singapore, Malay ethnicity was related to protection against DENV infections in a study with patients diagnosed between 2005 and 2013 [11].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Different ethnicities have been related to the risk of DENV infection. In Brazil, another study performed in Pernambuco identified that children born to mothers of Caucasian/Asian descent had a high risk of dengue [12]. In Singapore, Malay ethnicity was related to protection against DENV infections in a study with patients diagnosed between 2005 and 2013 [11].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have also associated socioenvironmental aspects with the number of dengue cases. Age, gender, ethnicity, education level or socioeconomic status, for example, have already been related to the risk of DENV infections [8][9][10][11][12][13][14][15]. In relation to environmental factors, uncontrolled urbanization and climatic conditions, such as temperature and rainfall, capable of influencing the population of vector mosquitoes, mainly Aedes aegypti and Ae.…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence reported in the present study is much lower than that reported in other studies. A study from a Brazilian birth cohort in the city of Recife which followed the children for first two years of life has reported an incidence of 107.6/1000 person years [18]. The Nicaraguan pediatric cohort study conducted in the city of Managua has reported an overall incidence of 90.2 infections/1000 person years.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported other associations, such as the presence and persistence of rheumatic pain and aging for CHIKV ( 30 ), and the possibility of death with DENV ( 29 , 31 ) and CHIKV ( 32 ) infections. Being a male child and an elderly man have been associated with DENV and CHIKV infections ( 33 , 34 ), but other studies have described an increased risk of CHIKV infection in older women ( 35 ) and increased risk of ZIKV and DENV infections in children of both sexes ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%